[tex]y=\dfrac{\ln x}{3x-6}[/tex]
Differentiate both sides with respect to [tex]x[/tex]:
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\frac{3x-6}x-3\ln x}{(3x-6)^2}[/tex]
When [tex]x=1[/tex], you have
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\frac{3-6}1-3\ln1}{(3-6)^2}=\dfrac{-3}9=-\dfrac13[/tex]
For part (b), we now assume that [tex]x[/tex] and [tex]y[/tex] are functions of an independent variable, which we'll call [tex]t[/tex] (for time). Now differentiating both sides with respect to [tex]t[/tex], we have
[tex]\dfrac{\mathrm dy}{\mathrm dt}=\dfrac{\frac{3x-6}x-3\ln x}{(3x-6)^2}\dfrac{\mathrm dx}{\mathrm dt}[/tex]
where the chain rule is used on the right side. We're told that [tex]y[/tex] is decreasing at a constant rate of 0.1 units/second, which translates to [tex]\dfrac{\mathrm dy}{\mathrm dt}=-0.1[/tex]. So when [tex]x=1[/tex], you have
[tex]-0.1=\dfrac{\frac{3-6}1-3\ln1}{(3-6)^2}\dfrac{\mathrm dx}{\mathrm dt}[/tex]
[tex]-0.1=-\dfrac13\dfrac{\mathrm dx}{\mathrm dt}[/tex]
[tex]\dfrac{\mathrm dx}{\mathrm dt}=0.3[/tex]
where the unit is again units/second.